THE PROPERTIES OF EDIBLE FILM DERIVED FROM BOVINE SPLIT HIDE GELATIN WITH ISOLATED SOY PROTEIN USING VARIOUS LEVELS OF GLYCEROL IN THE PRESENCE OF TRANSGLUTAMINASE - Dwi Wulandari; Yuny Erwanto; Yudi Pranoto; Rusman Rusman (Buletin Peternakan, 2017)
This study examined the characteristics of the edible film mixture gelatin bovine split hide and soy protein isolate, cross-linked using transglutaminase enzyme with addition level of glycerol as a plasticizer.The material used gelatin  combination (Gelatin bovine split hide: soy proteinisolate = 90: 10 with 30 Utransglutaminase enzyme levels ), and glycerol. Data were analyzed  using completely randomized design each treatment was replicated thrice of glycerol as a treatment level ( 10%, 20% dan 30%). The results showed that the glycerol level significantly affected the thickness, elongation, solubility, degree of cross-linking and WVTR, but not the tensile strength.The addition of glycerol causing the film becomes more elastic and  the surface is more homogeneous and compact. Increasing the level to 30% glycerol affects the mechanical properties of an edible film.